Recent development of fiber-optic chemical sensors and biosensors : mechanisms, materials, micro/nano-fabrications and applications - Yin, Ming-jie (2020)
The Internet-of-Things (IoT) has witnessed exponential growth over the past decade and will significantly reshape human life from every aspect, e.g., defense, environmental monitoring, energy, food safety, knowledge dissemination, healthcare and so on. Fiber-optic sensors, with both communication and sensing functions, have become a bridge to connect people and the whole world, so they are essential parts for accelerating the development of the IoT. Fiber-optic sensors possess the capability of translating a change of target analyte into optical signals and subsequently transmit an optical signal with target analyte information to people, machines or systems in real-time, even from a long distance. Therefore, exploration of high-performance fiber-optic chemical sensors and biosensors could significantly promote the development of the IoT. This review paper presents the foundations of fiber-optic chemical sensing or biosensing, including the sensing mechanisms of various fiber-optic sensors, sensing materials and the novel techniques for sensing materials deposition. Furthermore, recent developments on fiber-optic chemical sensors and biosensors are summarized, analyzed and discussed. Finally, the strategies and guidelines to further promote the development of fiber-optic sensors are also discussed.